The Relationship Between Gensini Score and Erectile Dysfunction in Patients with Chronic Coronary Syndrome. Issue 3 (2nd June 2021) - Deger, Mutlu; Ozmen, Caglar; Akdogan, Nebil; Tepe, Omer; Yucel, Sevinc Puren; Izol, Volkan
Abstract: Introduction: In previous studies, the relationship between atherosclerosis and erectile dysfunction (ED) was examined, but the relationship and correlation between Gensini score which evaluates the extent and severity of chronic coronary syndrome (CCS), and ED severity were not investigated. Aim: To evaluate the relationship between Gensini score and ED in patients with CCS. Methods: We included 142 consecutive male patients with the diagnosed CCS and underwent an elective coronary angiography between January 2019 and March 2020. Main Outcome Measure: Correlation analysis demonstrated that Gensini score significantly negatively correlated with the International Index Erectile Function - 5 (IIEF-5) score ( r  = -0.417, P < .001). Results: Severe ED was present in 48 (33.8%) patients, moderate ED in 31 (21.8%) patients, and mild ED in 22 (15.5%) patients. 41(28.9%) patients did not have ED. Both the No ED and Mild ED groups were statistically significantly lower than the Severe ED group in terms of the Gensini score ( P < .05). When the recommended optimal cut-off point and accuracy measurements were made for the Gensini score, the area under curve (AUC) value in predicting ED was 0.806 (95% CI: 0.732-0.880, P < .001). Multivariate logistic regression analysis demonstrated that independent predictors for ED were Gensini score and age ( P < .001, and P  = .026, respectively). Every 1 unit increase in Gensini score resulted in a 6% increase in the occurrence of ED (OR = 1.06, CI:1.03-1.10, P < .001). Conclusion: ED can be caused by endothelial dysfunction. Patients with severe CSS and high Gensini score should be evaluted for ED. ED may be a sign of severe CCS and a high Gensini score. It is also necessary to evaluate cardiological in patients with ED.